Internalization Mechanisms of the Epidermal Growth Factor Receptor after Activation with Different Ligands - Henriksen, Lasse (Public Library of Science, 2013)
The epidermal growth factor receptor (EGFR) regulates normal growth and differentiation, but dysregulation of the receptor or one of the EGFR ligands is involved in the pathogenesis of many cancers. There are eight ligands for EGFR, however most of the research into trafficking of the receptor after ligand activation focuses on the effect of epidermal growth factor (EGF) and transforming growth factor-α (TGF-α). For a long time it was believed that clathrin-mediated endocytosis was the major pathway for internalization of the receptor, but recent work suggests that different pathways exist. Here we show that clathrin ablation completely inhibits internalization of EGF- and TGF-α-stimulated receptor, however the inhibition of receptor internalization in cells treated with heparin-binding EGF-like growth factor (HB-EGF) or betacellulin (BTC) was only partial. In contrast, clathrin knockdown fully inhibits EGFR degradation after all ligands tested. Furthermore, inhibition of dynamin function blocked EGFR internalization after stimulation with all ligands. Knocking out a number of clathrin-independent dynamin-dependent pathways of internalization had no effect on the ligand-induced endocytosis of the EGFR. We suggest that EGF and TGF-α lead to EGFR endocytosis mainly via the clathrin-mediated pathway. Furthermore, we suggest that HB-EGF and BTC also lead to EGFR endocytosis via a clathrin-mediated pathway, but can additionally use an unidentified internalization pathway or better recruit the small amount of clathrin remaining after clathrin knockdown.